Determinan Gizi Lebih pada Remaja di SMP YPI Bintaro Jakarta - Sintha Fransiske Simanungkalit (Jurnal Ilmu Kesehatan Masyarakat, 2019)
Adolescence who entered the lives of children and adults, starting from the age of 9 – 10 years and ended at the age of 18 years. Adolescence included vulnerable groups in terms of physical, psychological, social, and nutrition. The purpose of this research is to know the determinant associated with nutritional state in adolescents in SMP YPI Bintaro Jakarta. This study used cross sectional design. The sample of this study used the students of SMP YPI Bintaro who fill the criteria. To obtain data over nutrition, anthropometry measurement of height and weight, FFQ sheet for vegetable and fruit consumption, also questionnaire for knowledge, peers, physical activity. Univariable data analysis used frequency distribution, bivariable used Chi Square Test. The result of this study found that the prevalence of over nutrition adolescents in this study population is 5% and shows consumption (p = 0.039), knowledge (p = 0.046) and physical activity (p = 0.039). Schools should cooperate with health institutions to educate on balanced nutrition and health, especially about over nutrition. Keyword : Adolescents, over nutrition, knowledge